Transconductance enhancement of a low voltage low power recycling folded cascode OTA using an asymmetrical current split input stage. (September 2019) - Khade, Amitkumar S.; Vyas, Vibha; Sutaone, Mukul; Musale, Sandeep
Abstract: This study presents a low power recycling folded cascode operational transconductance amplifier (RFC OTA) with enhanced transconductance. The proposed structure uses a novel input stage biased by a DC current source in addition to a floating voltage source. The adoption of a floating voltage source splits DC biasing current asymmetrically between the inner and outer differential pair of the input stage. This leads to an enhanced gain factor of recycling current mirrors resulting in improved transconductance. The uniqueness of the proposed structure is that a tuneable transconductance is achieved simply by adjusting the value of a floating voltage source. The proposed RFC OTA is simulated using 0.18 μm CMOS process. Simulation result shows 520% and 13.7 dB advancement in gain-bandwidth (GBW) product as well as gain compared to the FC OTA counterpart.